2016
DOI: 10.2174/1389201017666160127105926
|View full text |Cite
|
Sign up to set email alerts
|

An Interplay between Obesity and Inflammation in Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is traditionally defined as hyperglycemia first detected in pregnancy. The risk of GDM is much higher among obese women than in their lean counterparts. An excess of adipose tissue leads to immune and inflammatory responses of both white adipose tissue and the placenta, contributing to systemic inflammation. Although the significance of both obesity and inflammation is relatively well characterized in GDM, the molecular mechanisms involved are not fully defined and require f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Currently, it is believed that the toxic effects of alcohol on organs are mainly associated with the activity of alcohol metabolites, induction of oxidative stress, and translocation of intestinal endotoxins into the bloodstream [ 17 , 18 , 19 , 20 ]. These processes lead to cell damage and stimulation of inflammatory reactions releasing a large number of cytokines, among others such as TNF-alpha and IL-6 [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is believed that the toxic effects of alcohol on organs are mainly associated with the activity of alcohol metabolites, induction of oxidative stress, and translocation of intestinal endotoxins into the bloodstream [ 17 , 18 , 19 , 20 ]. These processes lead to cell damage and stimulation of inflammatory reactions releasing a large number of cytokines, among others such as TNF-alpha and IL-6 [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the current state of scientific knowledge, pre-pregnancy obesity and excessive gestational weight gain (EGWG) as well as gestational diabetes mellitus (GDM) have been regarded as independent risk factors for post-partum complications in both mothers and their children, which will subsequently lead to an increased risk of chronic diseases later in their lives [1,2,3,4,5]. It has been observed that women with a previous history of GDM and EGWG are much more prone to suffer from type 2 diabetes mellitus (T2DM), obesity, cardiovascular diseases (CVDs), and metabolic syndrome in the future [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The exact worldwide prevalence of GDM remains unknown, as systematically synthesized data on this issue are lacking, and the only available information is that the prevalence of GDM largely differs among countries and may even be different in the regions of the same country, ranging from 0.6% to 15%, depending on the ethnicity and socio-economic status of the studied individuals [ 2 ]. Women with a previous history of GDM have a significantly increased risk of developing type 2 diabetes mellitus (T2DM), obesity, and cardiovascular diseases (CVD) in the future [ 3 , 4 , 5 ]. The risk of developing diabetes is 9.6 times greater for patients with GDM, with the cumulative risk being 25% 15 years post-diagnosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%